2010
DOI: 10.1097/opx.0b013e3181d95b23
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Astigmatism in Native American Infants and Children

Abstract: As in non-Native American populations, Tohono O'odham infants show a high prevalence of astigmatism, which decreases in the second year of life. However, the prevalence of high astigmatism in Tohono O'odham children increases by age 2 to <3 years to a level near that seen in infancy and remains at that level until at least age 8 years. Longitudinal data are needed to determine whether the increase in high astigmatism after infancy occurs in infants who had astigmatism as infants or is due to the development of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
23
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 45 publications
5
23
4
Order By: Relevance
“…In Tohono O'odham children prevalence of corneal astigmatism 42.00 D was found to be lower in the 1 to 52-year-old age group when compared with all other age groups through age 7 years, except the 6 to 57-year-old group, 13 similar to the pattern seen with refractive astigmatism. 12 The presence of this pattern of decreased prevalence in corneal astigmatism in the 1 to 52 year age range data confirmed that, as found in previous reports, astigmatism arises primarily from the anterior cornea in Tohono O'odham children. 9,32 The present longitudinal analysis provided some interesting insights into the cause of the unexpected pattern we observed in cross-sectional data from this population, ie.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In Tohono O'odham children prevalence of corneal astigmatism 42.00 D was found to be lower in the 1 to 52-year-old age group when compared with all other age groups through age 7 years, except the 6 to 57-year-old group, 13 similar to the pattern seen with refractive astigmatism. 12 The presence of this pattern of decreased prevalence in corneal astigmatism in the 1 to 52 year age range data confirmed that, as found in previous reports, astigmatism arises primarily from the anterior cornea in Tohono O'odham children. 9,32 The present longitudinal analysis provided some interesting insights into the cause of the unexpected pattern we observed in cross-sectional data from this population, ie.…”
Section: Discussionsupporting
confidence: 90%
“…The longitudinal analysis focused only on children aged 6 months through 2 years suggests that the pattern of results observed in the cross-sectional data resulted from a combination of different developmental patterns observed in infants with high vs low/moderate astigmatism. Specifically, infants with high astigmatism in infancy tended to show reduced astigmatism in the second year of life (similar to that seen in other populations), 12,13 whereas infants with low to moderate astigmatism in infancy tended to remain stable in the second year of life, followed by a slight increase in the third year of life. Taken together, and viewed cross-sectionally, these patterns combine so that it appears that overall astigmatism decreases in the second year of life and then increases again.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations